2015
DOI: 10.1038/srep16369
|View full text |Cite
|
Sign up to set email alerts
|

Facile room-temperature synthesis of carboxylated graphene oxide-copper sulfide nanocomposite with high photodegradation and disinfection activities under solar light irradiation

Abstract: Carboxylic acid functionalized graphene oxide-copper (II) sulfide nanoparticle composite (GO-COOH-CuS) was prepared from carboxylated graphene oxide and copper precursor in dimethyl sulfoxide (DMSO) by a facile synthesis process at room temperature. The high-effective combination, the interaction between GO-COOH sheets and CuS nanoparticles, and the enhanced visible light absorption were confirmed by transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), X-ray powder diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 29 publications
(34 reference statements)
3
39
0
Order By: Relevance
“…form due to the existence of Cu 2+ vacancy [40,41]. Two strong peaks are consistent with the literature data of Cu + 2p 3/2 and 2p 1/2 [42,43,44]. On the sides of Cu + 2p 3/2 and 2p 1/2 peaks, two low-intensity components appeared, which can be assigned to the Cu 2+ oxidation state [45,46].…”
Section: Resultssupporting
confidence: 86%
“…form due to the existence of Cu 2+ vacancy [40,41]. Two strong peaks are consistent with the literature data of Cu + 2p 3/2 and 2p 1/2 [42,43,44]. On the sides of Cu + 2p 3/2 and 2p 1/2 peaks, two low-intensity components appeared, which can be assigned to the Cu 2+ oxidation state [45,46].…”
Section: Resultssupporting
confidence: 86%
“…The difference between the two peak position is Δ = 19.82 eV, which is in agreement with the literature. The most important point here is that we did not observe any satellite peak corresponding to Cu 2+ species ruling out the presence of CuO in our samples, even though we have O in our sample that is probably on the most top layer of the surface due to environmental exposure [46].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 89%
“…They showed that CuS prepared by this method had efficient catalytic activity, making it a cost-effective and convenient method for the treatment of dye-contaminated wastewater. Yu, et al [22] reported that carboxylic acid functionalized graphene oxide-copper (II) sulfide nanoparticle composite (GO-COOHCuS) was prepared from carboxylated graphene oxide and copper precursor in dimethyl sulfoxide (DMSO) by a facile synthesis process at room temperature. They reported their application to the photocatalytic degradation of phenol and Rhodamine B (RhB), as well as the inactivation of Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis) under solar light irradiation using the as-synthesized materials as the photocatalysts.…”
Section: Introductionmentioning
confidence: 99%